Total Synthesis of Oxepin and Dihydrooxepin Containing Natural Products - Sokol, Kevin Rafael; Magauer, Thomas (Synthesis, 2021)
The construction of oxepin and dihydrooxepin containing natural products represents a challenging task in total synthesis. In the last decades, a variety of synthetic methods have been reported for the installation of these structural motifs. Herein, we provide an overview of synthetic methods and strategies to construct these motifs in the context of natural product synthesis and highlight the key steps of each example.1 Introduction2 Oxepin Natural Products3 Dihydrooxepin Natural Products3 Brønsted or Lewis acid Catalyzed Cyclization3.2 Radical Cyclization3.3 Substitution and Addition Cyclization3.4 Sigmatropic Rearrangement3.5 Oxidative Methods3.6 Transition Metal Catalyzed Cyclization4 Summary
Keywords: oxepin; dihydrooxepin; natural product; total synthesis; heterocycles